EARTHQUAKE HAZARD ALONG THE WESTERN COAST OF SOUTH AMERICA INFERRED FROM CONDITIONAL PROBABILITIES - Koravos, G.; Vougiouka, G.; Tsapanos, T.M.; Drakatos, G.; Olasoglou, E. (Bulletin of the Geological Society of Greece, 2016)
The conditional probabilities method is considered to be an alternative approach in order to estimate the earthquake hazard. For this purpose, this technique was applied to the western side of South America, one of the most seismogenic regions of the world. The method is applied in six pre-determined zones which covered the whole examine area. The occurrence of the earthquakes as a function of time was assessed, using the conditional probabilities technique. The Kolmogorov-Smirnov test was applied in order to determine the distribution followed by the inter-arrival times between the successive past events. The test shows that the lognormal is the best fit distribution, for the scope of the present work. The obtained results are in good accordance to the method applied. High probabilities are estimated for events with Mw7.0. For the whole western part of South America, there is a probability about 64% for an earthquake occurrence with magnitude M8.0, during a time period of 20 years. Higher probability (≈73%) was estimated for a time period of 50 years and for an earthquake of magnitude M8.5. This is clearly showed for the event of 1960, where the next (a posteriori procedure) earthquake of M=8.8 occurred on 2010.